Under pressure: Effect of sedimentary compression on the iliac morphology of early sauropodomorphs. (December 2018) - Müller, Rodrigo Temp; Garcia, Maurício Silva; Da-Rosa, Átila Augusto Stock; Dias-da-Silva, Sérgio
Abstract: Sedimentary compression can produce deep changes in the organismal morphology during fossil diagenesis, so that intrinsic biological aspects (e.g. internal architecture of bones) could also generate non-natural traits when determinate bone element suffers sedimentary compression. Here we report a particular taphonomic case, in which the mode of preservation of a basal sauropodomorph from the Late Triassic of Brazil offers a valuable opportunity to examine the effects of sedimentary compression on a specific doubled body part of a single individual. The specimen is associated with two other almost complete and articulated individuals, comprising a monotypic association. The specimen herein studied presents the left ilium and hindlimb disarticulated from its body, where the right ilium was preserved with its ventral surface ventrally directed, and, conversely, the lateral surface of the left one was ventrally directed. Thus, their distinct placement in the substrate resulted in two distinct taphonomic histories reflected in their dissimilar shapes. This corresponds to a particular case of taphomorphic differences expressed in a single individual. Indeed, some of the peculiar traits of each ilium also occur in other specimens of close related taxa that experienced similar taphonomic histories. Sedimentary compression may produce dissimilar shapes in different portions of the skeleton, and incorrect observations generate what we call "taphoanatomical features", traits shared among close phylogenetic taxa/specimens resulting from similar taphonomic processes in response to specific biological aspects of the skeleton, not necessarily expressing phylogeny. Failing to recognize these trends could affect anatomical interpretations, especially regarding their role in a phylogenetic context. Highlights: We present a peculiar case of taphomorphy in a single specimen of sauropodomorph. Both ilia present dissimilar shape in response of distinct placement on the substrate. Sedimentary compression is pointed as responsible by its disparity. The specimen is used to investigates the effects of compression in other specimens. Thus, several traits resulted by similar taphonomic histories are suggested.